2017
DOI: 10.1111/ocr.12185
|View full text |Cite
|
Sign up to set email alerts
|

Centre‐level variation in dental treatment and oral health and individual‐ and area‐level predictors of oral health in 5‐year‐old children with non‐syndromic unilateral cleft lip and palate: the Cleft Care UK study. Part 3

Abstract: The association with use of fluoride tablets and varnish probably reflects reverse causality but indicates the need for early preventative interventions in children with UCLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 34 publications
2
21
1
1
Order By: Relevance
“…In this supplement, we have explored centre‐level variability across a range of treatment and outcome measures. Our results, which are reported in full in each respective paper in this supplement, suggest that there was centre‐level variation in several of these treatment indicators and outcomes across the domains of oral health, audiology and speech . Describing and exploring these centre‐level variations is important for several reasons.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In this supplement, we have explored centre‐level variability across a range of treatment and outcome measures. Our results, which are reported in full in each respective paper in this supplement, suggest that there was centre‐level variation in several of these treatment indicators and outcomes across the domains of oral health, audiology and speech . Describing and exploring these centre‐level variations is important for several reasons.…”
Section: Discussionmentioning
confidence: 67%
“…We have described a standard hierarchical statistical model to predict centre‐level means and centre‐level variation and highlighted how to interpret the output from these models using the expository examples of facial growth and appearance. We found modest differences between centres in the age at assessment and gender of the children over and above that which may be expected from sampling variation and so we controlled for these differences in the analysis presented in this paper and in the subsequent papers in this supplement . We found no evidence of centre‐level variation in dento‐alveolar relationships and facial appearance.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this supplement, we report further on a UK‐wide cross‐sectional survey of 5‐year‐old children with unilateral cleft lip and palate conducted between January 2011 and December 2012—Cleft Care UK (CCUK) that we have described previously . We have already shown that some outcomes (such as facial growth, speech and parental report of self‐confidence) have improved following centralization while some outcomes (such as oral health and hearing) have not changed .…”
Section: Introductionmentioning
confidence: 82%
“…We have summarized the centre‐level variation for all treatments and outcomes in Table . We found centre‐level variation for some treatments such as early grommet placement (VPC 18%, P <.001), fitting of hearing aids (VPC 8%, P =.03), fluoride treatment (eg, VPC for fluoride tablets: 57%, P <.001), secondary speech surgery (VPC 15% P <.001) and treatment for cleft speech characteristics (VPC 9% P =.006) . There was also centre‐level variation for some outcomes such as intelligibility of speech (VPC 13%, P =.001) with the centres with the best results having half the number of children with poor intelligibility of speech .…”
Section: Centre‐level Variationmentioning
confidence: 95%